Reconstruction of the ancestral metazoan genome reveals an increase in genomic novelty - Jordi Paps; Peter W. H. Holland (Nature Communications, 2018)
Animals, the Metazoa, co-opted numerous unicellular genes in their transition to multicellularity. Here, the authors use phylogenomic analyses to infer the genome composition of the ancestor of extant animals and show there was also a burst of novel gene groups associated with this transition.